1994
DOI: 10.1111/j.2042-7158.1994.tb03759.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hypolipidaemics cetaben and clofibrate on mitochondrial and peroxisomal enzymes of rat liver

Abstract: Clofibrate or cetaben was administered to male rats for 10 days. Peroxisomal and mitochondrial enzymes were assayed in liver subcellular fractions. Clofibrate affected the specific activities of both mitochondrial enzymes (glycerol-3-phosphate dehydrogenase and nicotinamide-linked isocitrate dehydrogenase) and peroxisomal enzymes (fatty acyl-CoA oxidase, glycerone phosphate acyltransferase, urate oxidase, and D-amino-acid oxidase). In contrast, cetaben raised only the peroxisomal enzymes, acyl-CoA oxidase, gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1995
1995
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The gene expression pattern of isocitrate dehydrogenase was different in the treatment with clofibrate and gemfibrozil. Previous studies have also shown that isocitrate dehydrogenase was activated by clofibrate [6,14], but we have found that the expression of isocitrate dehydrogenase is decreased by gemfibrozil (Table 1). Previous research has identified that cytochrome P450 subfamilies were induced by peroxisome proliferators in liver of male Sprague-Dawley rats [10].…”
Section: Resultsmentioning
confidence: 44%
“…The gene expression pattern of isocitrate dehydrogenase was different in the treatment with clofibrate and gemfibrozil. Previous studies have also shown that isocitrate dehydrogenase was activated by clofibrate [6,14], but we have found that the expression of isocitrate dehydrogenase is decreased by gemfibrozil (Table 1). Previous research has identified that cytochrome P450 subfamilies were induced by peroxisome proliferators in liver of male Sprague-Dawley rats [10].…”
Section: Resultsmentioning
confidence: 44%
“…Intracellular very-long-chain fatty acid uptake would have been blocked if an inhibition in gene expression of the latter enzyme had occurred [34] and hence would have dramatically inhibited the peroxisomal oxidizing activity. The induction of palmitoyl-CoA oxidase by CLO was established to be a stimulation of peroxisomal functioning [35]. Therefore, the higher activity of palmitoyl-CoA oxidase in EC group vs. CC was probably aimed at the degradation of the abnormally elevated concentration of Mead acid which so far has not been reported to have physiological function.…”
Section: Discussionmentioning
confidence: 91%
“…Regardless of iron status, clofibrate treatment caused m-ACO activity to increase by 133%, while clofibrate also enhanced the activity of three rate-limiting enzymes in the TCA cycle, citrate synthase, nicotinamide-linked isocitrate de-hydrogenase, and ␣-ketoglutarate dehydrogenase, by 24, 54, and 153%, respectively (Prager et al, 1993;Schon et al, 1994). In the clofibrate-treated liver, the production of acetyl-CoA is elevated and leads to increased citrate formation via citrate synthase (Ball et al, 1979).…”
Section: Metabolic Adaptations Of M-acomentioning
confidence: 99%